Improvement of in vitro osteogenesis and antimicrobial activity of injectable brushite for bone repair by incorporating with Se-loaded calcium phosphate. Issue 8 (15th April 2021) - Pei, Zhengjun; Zhang, Zilin; Li, Guangda; Fu, Fangfang; Zhang, Kaili; Cai, Yunbian; Yang, Yunchuan
Abstract: The main objective of this research is to study the effect of selenium (Se) on injectable brushite cement (Bru) derived from Se-loaded cement starting calcium phosphate powder (SP) to reveal whether injectable Se-loaded Bru has potential for bone repair. Se was incorporated into Bru by cement SP with a Se/P molar ratio of 0.05, 0.10, and 0.15, respectively. The results show that although the cement SP changes from β-calcium phosphate to hydroxyapatite as the Se content increases, brushite is still the dominant crystalline phase of the cements. The increase of Se concentration prolongs the cement setting time and promote the cement injectability, however, excellent anti-washout ability and degradability is observed for all the cements. Moreover, the cements with higher content of Se release out Se faster when soaking in phosphate buffer saline. The cell experimental results show that cements with a Se/P of 0.05 and 0.10 can not only be beneficial for osteoblastic MG63 cells adhesion and proliferation but also enhance cell mineralization property, while the cement with a Se/P ratio of 0.15 shows cytotoxicity. Furthermore, both the agar plate tests and the broth antimicrobial tests reveal that Se-loaded Bru can significantly inhibit the growth of E. coil, S. aureus, and P. aeruginosa . The antibacterial activity increases with the increase of Se concentration in the cement. Therefore, the biological performance of injectable Se-loaded brushite cement is dose-dependent and brushite cement with an appropriate dose of Se has potential for bone repair application.